2019
DOI: 10.1590/18069657rbcs20180133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZnO Nanoparticles and a Non-Nano ZnO on Survival and Reproduction of Earthworm and Springtail in Tropical Natural Soil

Abstract: In recent years, various studies and development using nanoparticles (NPs) have been carried out in the most diverse areas of knowledge. Although nanomaterials are widely employed by many sectors and some may have a fertilizing potential, little is known about their effects on the environment. This study aimed to evaluate the effect of applying, in tropical natural soil, different contents of nanoparticles of zinc oxide (NPs-ZnO) and non-nano zinc oxide (ZnO) on soil pH and on the survival and reproduction rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Absence of effect on lethality in edaphic organisms has already been reported in studies published in the literature evaluating the toxicity of other nanoparticles with fertilizer effect. Recent studies have shown that zinc oxide nanoparticles (ZnO‐NPs) do not cause significant damage to earthworms of the species E. fetida and E. andrei (Alves et al, 2019; Romero‐Freire et al, 2016; Yadav, 2017). However, even nanoparticles with antibacterial effect such as aluminum oxide (Al 2 O‐NPs) and titanium oxide (TiO 2 ‐NPs) did not cause lethality in earthworms, but affected the reproduction rate and behavior of earthworms of the species E. fetida , when used at high levels that are unlikely to be found in the environment, exceeding 2500 and 5000 mg kg −1 for Al 2 O‐NPs and for TiO 2 ‐NPs, respectively (Cañas et al, 2011; Coleman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Absence of effect on lethality in edaphic organisms has already been reported in studies published in the literature evaluating the toxicity of other nanoparticles with fertilizer effect. Recent studies have shown that zinc oxide nanoparticles (ZnO‐NPs) do not cause significant damage to earthworms of the species E. fetida and E. andrei (Alves et al, 2019; Romero‐Freire et al, 2016; Yadav, 2017). However, even nanoparticles with antibacterial effect such as aluminum oxide (Al 2 O‐NPs) and titanium oxide (TiO 2 ‐NPs) did not cause lethality in earthworms, but affected the reproduction rate and behavior of earthworms of the species E. fetida , when used at high levels that are unlikely to be found in the environment, exceeding 2500 and 5000 mg kg −1 for Al 2 O‐NPs and for TiO 2 ‐NPs, respectively (Cañas et al, 2011; Coleman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another study in soil showed little effect on earthworm (E. andrei) survival at concentrations up to 4000 mg kg -1 , (EC50 estimated as 1020 mg kg -1 ). However, reproduction and the number of juvenile offspring were significantly affected (Alves et al, 2019). Another study was published that reports longterm exposure (140 days) of ZnO-NPs to earthworms in different soil types (entisol and tropical artificial soil).…”
Section: Zinc Oxidementioning
confidence: 99%
“…The results indicate that the ZnO nanoparticles induced changes that increased the pH of the ultisol and loam soils. Several studies indicate that ENPs such as copper oxide nanoparticles [8], zero-valent iron nanoparticles [10] and ZnO nanoparticles [7,9] induced changes in soil pH during acute and chronic exposures. These results are consistent with the present study in which ZnO nanoparticles raised the pH of the ultisol and loam soils.…”
Section: Effect Of Zno Nanoparticles On Soil Ph Hydrogen Ion Exchanmentioning
confidence: 99%
“…The effect on soil properties can vary, for example, the soil pH is influenced by the accumulation of different types of nanoparticles [6]. Several studies [7,8,9,10] have reported increased pH of soils on exposure to different nanoparticles. Soil pH determines the function of a soil and is closely related to presence of, and absorption of nutrients, microbial activity and plant growth [8].…”
Section: Introductionmentioning
confidence: 99%